Experimental Investigation into the Effects of Wave Direction on Seakeeping Performances of Ship - Soetardjo, Ir. Meitha (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
In early design stage of ship form design, there are some aspects need to be considered for estimation and evaluation of seakeeping of the ship. This study describes the influence of wave directions on ship motions and the effect of speed on the characteristics of ship seakeeping. In response to this study, various tests of seakeeping in irregular waves are performed in wave basin. The seakeeping tests comprise motions and accelerations tests. Experimental results are presented in tables and graphical form and the ship performances are discussed and compared with recently published data. Results presented in this paper offer practical data and may prove useful for designers at conceptual or preliminary design stages.